1981
DOI: 10.3181/00379727-166-41053
|View full text |Cite
|
Sign up to set email alerts
|

Fenfluramine Effects on Insulin Resistance and Lipogenesis in Genetically Obese (ob/ob) Mice

Abstract: Treatment of 15-week-old obese and lean mice with the amphetamine derivative fenfluramine (15,25, and 40 mg/kg body wt, ip) for 14 days did not reduce body weight, except in lean mice receiving 40 mg/kg. In vivo insulin sensitivity, measured as the ability of exogenous insulin (1 IUIkg body wt, ip) to lower blood glucose, was improved in obese mice receiving the two higher doses (25 and 40 mg/kg) of fenfluramine for 14 days, when compared to untreated obese mice. There was no change in insulin sensitivity betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1983
1983
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…In contrast, no effect was seen either with or without insulin in a hind limb perfusion in rats (6). In the intact organism, improved insulin sensitivity was observed after chronic fenfluramine in obese {ob/ob) mice (7). Similarly, fenfluramine improved glycemic control in obese glucose-intolerant humans and in non-insulin-dependent diabetes mellitus (NIDDM) independent of its effects on food intake and body weight (8).…”
mentioning
confidence: 99%
“…In contrast, no effect was seen either with or without insulin in a hind limb perfusion in rats (6). In the intact organism, improved insulin sensitivity was observed after chronic fenfluramine in obese {ob/ob) mice (7). Similarly, fenfluramine improved glycemic control in obese glucose-intolerant humans and in non-insulin-dependent diabetes mellitus (NIDDM) independent of its effects on food intake and body weight (8).…”
mentioning
confidence: 99%
“…Одним из таких препаратов является п-этила-метил-3-флюорометилфенэтиламина гидрох лорид (минифаж, пондерал), оказывающий сти мулирующее действие на центральную нервную систему [2]. Фенфлюрамин уменьшает запас и синтез моноаминов (5-гидрокситриптамина) в диэнцефальных отделах мозга [8] [7] в экспериментах на крысах подтвердил, что данный эффект препара та осуществляется за счет улучшения чувстви тельности периферических тканей к инсулину, в особенности мышц.…”
Section: выводыunclassified
“…It is structurally related to the trifluormethyl molecule fenfluramine. Evidence suggests that fenfluramine improves insulin action, independent of its effects on food intake and body weight, in normoglycemic obese animal models (4,5). It also has been reported that chronic fenfluramine treatment improved glycemic control in obese, glucose-intolerant and NIDDM humans, independent of its anoretic effect (6,7).…”
mentioning
confidence: 94%